From the Trinity : the coming of God in Revelation and theology - Coda, Piero, 1955- (The Catholic University of America Press, 2020)
"Provides an overall view of the history and the philosophical and theological significance of God the Trinity from religious, anthropological, and sociocultural perspectives, following the generative-progressive method advocated by the Second Vatican Council"--